ANIMATED POSTERS: HISTORY AND GENESIS - Sosnytskyi, Yurii (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2025)
Animated posters are a relatively new communication form that combines graphic design and animation, creating new opportunities for audience engagement. Although animated posters are gaining popularity, there is a lack of research highlighting their historical origins and development features. The study aims to analyze the history and genesis of animated posters in graphic design to identify the stages of their formation, key characteristics, and factors that contributed to their development. The tasks are to review the origins of poster graphic design and analyze the stages of animation development in graphic design; to identify the main characteristics of animated posters and examine the specifics of their evolution; to analyze the impact of technological changes on the development of animated posters and their role in modern media. The research methodology is based on qualitative and quantitative analysis, including an online survey among the target audience and a review of existing examples of animated posters. Two surveys were conducted, with 42 respondents divided into three groups, each evaluating two sets of questions. Informal interviews with experienced designers were also held to gain practical insights into animated design, supplemented by a literature review and an in-depth analysis of 15 case studies, focusing on the frame and timing aspects as key components of motion design. Discussion. The findings confirm the effectiveness of animated posters in capturing attention and improving information retention compared to static images. Comparative analysis with previous studies on animated typography and motion graphics highlights the effectiveness of short animations lasting 10–15 seconds, particularly for social networks and mobile platforms. Designers also support the integration of augmented reality (AR) into posters for enhanced audience interaction, though further experiments with AR elements are needed to determine optimal approaches for poster design. Conclusions. Animated posters have evolved from traditional forms, gaining dynamic and interactive features that attract audience attention. Technological advancements have enriched graphic design's communicative potential by allowing the blending of text, images, sound, and motion to create interactive and engaging content. Integrating augmented reality and virtual reality into posters offers new opportunities for audience engagement and education, creating an ecosystem where image, animation, and digital design intersect. Thus, animated posters emerge as an important medium with potential for future development through the integration of modern technologies into visual communications